2018
DOI: 10.31233/osf.io/wqjpb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simbirskiasaurus and Pervushovisaurus reassessed: implications for the taxonomy and cranial osteology of Cretaceous platypterygiine ichthyosaurs

Abstract: The ichthyosaur fossil record is interspersed by several hiatuses, notably during the Cretaceous. This hampers our understanding of the evolution and extinction of this group of marine reptiles during the last 50 million years of its history. Several Cretaceous ichthyosaur taxa named in the past have subsequently been dismissed and referred to the highly inclusive taxon Platypterygius, a trend that has created the impression of low Cretaceous ichthyosaur diversity. Here, we describe the cranial osteology, reas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 39 publications
(87 reference statements)
2
24
0
1
Order By: Relevance
“…The crown surface shows fine pits in the apical area, a condition previously reported in other ophthalmosaurids such as 'Platypterygius' hercynicus (Fischer, 2012), Aegirosaurus (Fischer et al, 2011) and in 'Platypterygius' sp. (Fischer et al, 2014). The presence of longitudinal ridges on the basal enamel surface recalls the condition described by Fischer et al (2012) for Acamponectes densus.…”
Section: Ichthyosauriasupporting
confidence: 66%
See 1 more Smart Citation
“…The crown surface shows fine pits in the apical area, a condition previously reported in other ophthalmosaurids such as 'Platypterygius' hercynicus (Fischer, 2012), Aegirosaurus (Fischer et al, 2011) and in 'Platypterygius' sp. (Fischer et al, 2014). The presence of longitudinal ridges on the basal enamel surface recalls the condition described by Fischer et al (2012) for Acamponectes densus.…”
Section: Ichthyosauriasupporting
confidence: 66%
“…The Cretaceous period saw the diversification and widespread geographic dispersal of several groups of emblematic marine tetrapods, including marine turtles, marine crocodylomorphs, ichthyosaurs, plesiosaurs and mosasaurs (e.g., Bardet et al, 2014;Fischer et al, 2014;Martin et al, 2014;Nicholson et al, 2015). In parallel, geochemical studies have shown that this time interval was characterized by very warm conditions, punctuated by episodes of exceptional warmth (early Aptian, Cenomanian-Turonian) and transient cooling (late Valanginian, late Aptian and early Maastrichtian; Pucéat et al, 2003;Bodin et al, 2015;O'Brien et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This method has proved useful here as a faster addition to a priori STR (Wilkinson 1995;Siu-Ting et al 2015). Previous studies of ichthyosaurs have used an arbitrary proportion of incomplete characters to remove taxa, presenting this alongside the complete analysis (Fischer et al 2013;Fischer et al 2014a). Although this is the simplest method, it does not always prove the best in resolving relationships (Wiens 2003).…”
Section: Phylogeny Reconstructionsmentioning
confidence: 99%
“…This unprecedented quantity and quality of material has facilitated comprehensive appraisals of craniodental (Kear, 2005c;Maxwell et al, 2011) and postcranial anatomy (Zammit et al, 2010) that are now a comparative standard for Cretaceous ichthyosaurian remains worldwide (e.g. Maxwell and Kear, 2010;Maxwell et al, 2012;Fischer et al, 2014). Moreover, functional analyses and feeding traces have permitted reconstruction of locomotory modes (Zammit et al, 2014), jaw musculature and sense organs (Kear, 2005c), and dietary specialisation towards small-bodied prey including bony fish (Wretman and Kear, 2014) and aquatic amniotes (e.g.…”
Section: Ichthyosauriansmentioning
confidence: 99%